A pervasive tele-health system for continual and low intrusive monitoring using peer-to-peer networks. (26th March 2009) - Le, Hanh; Schiff, Nina; Du Plessis, Johan; Hoang, Doan B.
There are many people suffering from chronic illnesses, obesity and related diseases such as: high blood pressure, arrhythmia, diabetes, etc. However, with a large number of patients and constant health monitoring requirements, a centralised server will not be able to accommodate such high volumes of data. In this paper, the authors propose to develop a pervasive electronic healthcare system using peer-to-peer (P2P) networks. The authors developed a heart monitoring application as their first prototype to demonstrate the concept. The main advantage of the model is scalability and cost efficiency.